Effect of iron supplementation in patients with heart failure and iron deficiency: A systematic review and meta-analysis. (October 2021) - Yamani, Naser; Ahmed, Aymen; Gosain, Priyanka; Fatima, Kaneez; Shaikh, Ali Tariq; Qamar, Humera; Shahid, Izza; Arshad, Muhammad Sameer; Almas, Talal; Figueredo, Vincent
Abstract: Background: The effectiveness of oral and intravenous iron supplementation in reducing the risk of mortality and hospitalizations in HF patients with iron deficiency is not well-established. Methods: A thorough literature search was conducted across 2 electronic databases (Medline and Cochrane Central) from inception through March 2021. RCTs assessing the impact of iron supplementation on clinical outcomes in iron deficient HF patients were considered for inclusion. Primary end-points included all-cause mortality and HF hospitalization. Evaluations were reported as odds ratios (ORs) or risk ratios (RRs) with 95% confidence intervals (CI) and analysis was performed using a random effects model. I 2 index was used to assess heterogeneity. Results: From the 2599 articles retrieved from initial search, 10 potentially relevant studies (n = 2187 patients) were included in the final analysis. Both oral (OR: 0.93; 95% CI: 0.08–11.30; p = 0.951) and intravenous (OR: 0.97; 95% CI: 0.73–1.29; p = 0.840) iron supplementation did not significantly reduce all-cause mortality. However, intravenous iron supplementation significantly decreased the rates of overall (OR: 0.52; 95% CI: 0.33–0.81; p = 0.004) and HF (OR: 0.42; 95% CI: 0.22–0.80; p = 0.009) hospitalizations. In addition, intravenous ferric carboxymaltose therapy significantly reduced the time to first HF hospitalization or cardiovascular mortality (RR = 0.70; 95% CI = 0.50–1.00; p = 0.048), but had no effect on time to first cardiovascular death (RR: 0.94; 95% CI: 0.70–1.25; p = 0.655). Conclusion: Oral or intravenous iron supplementation did not reduce mortality in iron deficient HF patients. However, intravenous iron supplementation was associated with a significant decrease in overall and HF hospitalizations.